Economic burden in non‐Hodgkin lymphoma survivors: The French Lymphoma Study Association SIMONAL cross‐sectional study - Nerich, Virginie; Guyeux, Christophe; Henry‐Amar, Michel; Couturier, Raphaël; Thieblemont, Catherine; Ribrag, Vincent; Tilly, Hervé; Haioun, Corinne; Casasnovas, René‐Olivier; Morschhauser, Franck; Feugier, Pierre; Sibon, David; et al. (Cancer, 2022)
Background No study has focused on the economic burden in non‐Hodgkin lymphoma (NHL) survivors, even though this knowledge is essential. This study reports on health care resource use and associated health care costs as well as related factors in a series of 1671 French long‐term NHL survivors. Methods Health care costs were measured from the payer perspective. Only direct medical costs (medical consultations, outpatient treatments, hospitalizations, and medical transport) in the past 12 months were included (reference year 2015). Multiple linear regression was used to search for explanatory factors of health care costs. Results In total, 1100 survivors (66%) reported having used at least 1 health care resource, and 867 (52%) reported having used at least 1 outpatient treatment. After the authors accounted for missing data, the mean health care cost was estimated at €702 ± €2221. Hospitalizations and outpatient treatments were the main cost drivers. Sensitivity analyses confirmed the robustness of the results. For the 1100 survivors who reported using at least 1 health care resource, the mean health care cost was €1067 ± €2268. Several factors demonstrated statistically significant relationships with health care costs. For instance, cardiovascular disorders increased costs by 66% ± 16%. In contrast, rituximab or autologous stem cell transplantation as initial therapy had no effect on health care costs. Conclusions The consideration of economic constraints in health care is now a reality. This retrospective study reports on a better understanding of health care resource use and associated health care costs as well as related factors. It may help health care professionals in their ongoing efforts to design person‐centered health care pathways. Improvements in the management of non‐Hodgkin lymphoma (NHL) have led to longer survival with potentially increased health care consumption and costs. This cross‐sectional study in long‐term NHL survivors shows that health care resource use and associated costs are linked to sociodemographic factors and comorbidities with no influence from previous lymphoma treatments (chemotherapy, rituximab, and transplantation).